2008
DOI: 10.1111/j.1600-051x.2008.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant diseases: Consensus Report of the Sixth European Workshop on Periodontology

Abstract: Issues related to peri-implant disease were discussed. It was observed that the most common lesions that occur, i.e. peri-implant mucositis and peri-implantitis are caused by bacteria. While the lesion of peri-implant mucositis resides in the soft tissues, periimplantitis also affects the supporting bone. Peri-implant mucositis occurs in about 80% of subjects (50% of sites) restored with implants, and peri-implantitis in between 28% and 56% of subjects (12-40% of sites). A number of risk indicators were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
1,192
3
102

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,233 publications
(1,312 citation statements)
references
References 3 publications
15
1,192
3
102
Order By: Relevance
“…In the 7th European Workshop, it was diagnosed as bleeding on gentle probing (Lang, Berglundh, & Working Group 4 of Seventh European Workshop on Periodontology, 2011). Peri‐implantitis is defined as inflammation of the soft tissues in combination with ongoing loss of the supporting peri‐implant bone beyond the physiological bone adaptation (Lindhe, Meyle, & Group D of European Workshop on Periodontology, 2008). The latter takes place as a consequence of biologic width establishment during initial healing.…”
Section: Introductionmentioning
confidence: 99%
“…In the 7th European Workshop, it was diagnosed as bleeding on gentle probing (Lang, Berglundh, & Working Group 4 of Seventh European Workshop on Periodontology, 2011). Peri‐implantitis is defined as inflammation of the soft tissues in combination with ongoing loss of the supporting peri‐implant bone beyond the physiological bone adaptation (Lindhe, Meyle, & Group D of European Workshop on Periodontology, 2008). The latter takes place as a consequence of biologic width establishment during initial healing.…”
Section: Introductionmentioning
confidence: 99%
“…10 Peri-implant mucositis may affect up to 50% of implants and is characterised by bleeding on probing. 11 Peri-implant mucositis usually resolves with improved homecare, antiseptic mouthwash and careful mechanical cleaning. 11,12 A lack of keratinised mucosa may impair oral hygiene procedures and increase the incidence of peri-implant mucositis.…”
Section: Peri-implant Mucositismentioning
confidence: 99%
“…10,14 Peri-implantitis is characterised by marginal bone loss and may be associated with bleeding on probing, suppuration, pocket formation and mucosal recession. 11 Marginal bone loss during the first year of function is attributed to remodelling and peri-implantitis cannot be diagnosed until after this time. 10 It has been suggested that peri-implantitis may be diagnosed when the bone adjacent to ≥3 threads of an implant is lost after one year in function.…”
Section: Peri-implantitismentioning
confidence: 99%
“…This can cause a need for bone augmentation for the new future implant. 38 In contrast to a failed endodontic treatment, this can be retreated and surgically treated without any damages to the future treatment. 39 The chance of having a tooth extracted after failure from initial treatment, retreatment and apical surgery is only 1in 500 cases.…”
Section: Inmentioning
confidence: 99%